Criminal Liability in the Energy Sector Corruption Scandal: A Legal Analysis of Abuse of Authority in State-Owned Enterprises - Assaad, A. Istiqlal (PT. Anagata Sembagi Education, 2026)
Corruption in the energy sector involving State-Owned Enterprises (SOEs) is a form of abuse of authority that significantly impacts state financial losses and weakens corporate governance. The complexity of energy sector management, which involves strategic business decisions, often raises debates about the boundaries between legitimate business risks and unlawful acts that can be qualified as corruption. This condition creates the need for a legal review of the construction of criminal liability of SOE officials in energy sector management. This study aims to analyze the legal construction of abuse of authority in corruption in the management of SOEs in the energy sector and examines the forms of criminal liability of SOE officials from the perspective of criminal law and corporate governance. The research method used is normative legal research with a statutory approach, a conceptual approach, and a case approach analyzed qualitatively. The results show that the criminal liability of SOE officials is determined by the fulfillment of the elements of fault, a causal relationship, and the existence of abuse of authority that causes state losses. The business judgment rule principle can provide legal protection for business decisions taken in good faith and based on the principle of prudence, but does not apply if there is a conflict of interest, bad faith, or a violation of the principles of good corporate governance. Therefore, it is necessary to construct a criminal liability model that is able to clearly distinguish between legitimate business risks and abuse of authority so that corruption eradication remains effective without hindering legitimate business decision-making in the management of state-owned enterprises in the energy sector.